Diversity, structure and spatial distribution of megabenthic communities in Cap de Creus continental shelf and submarine canyon (NW Mediterranean). (November 2022) - Dominguez-Carrió, Carlos; Riera, Joan Lluís; Robert, Katleen; Zabala, Mikel; Requena, Susana; Gori, Andrea; Orejas, Covadonga; Lo Iacono, Claudio; Estournel, Claude; Corbera, Guillem; Ambroso, Stefano; Uriz, Maria Jesús; et al.
Graphical abstract: Highlights: Cap de Creus shelf and submarine canyon host a diverse benthic ecosystem. Over 165 (morpho)species identified in the images, organized in nine megabenthic communities. These include CWCs, octocoral gardens, sponge grounds and echinoderm aggregations. Spatial distribution is mainly determined by depth, substrate type & bottom currents. Abstract: The continental shelf and submarine canyon off Cap de Creus (NW Mediterranean) were declared a Site of Community Importance (SCI) within the Natura 2000 Network in 2014. Implementing an effective management plan to preserve its biological diversity and monitor its evolution through time requires a detailed characterization of its benthic ecosystem. Based on 60 underwater video transects performed between 2007 and 2013 (before the declaration of the SCI), we thoroughly describe the composition and structure of the main megabenthic communities dwelling from the shelf down to 400 m depth inside the submarine canyon. We then mapped the spatial distribution of the benthic communities using the Random Forest algorithm, which incorporated geomorphological and oceanographic layers as predictors, as well as the intensity of the bottom-trawling fishing fleet. Although the study area has historically been exposed to commercial fishing practices, it still holds a rich benthic ecosystem with over 165 different invertebrate (morpho)species of the megafauna identified in the video footage, which form up to 9 distinct megabenthic communities. The continental shelf is home to coral gardens of the sea fan Eunicella cavolini, sea pen and soft coral assemblages, dense beds of the crinoid Leptometra phalangium, diverse sponge grounds and massive aggregations of the brittle star Ophiothrix fragilis . The submarine canyon off Cap de Creus is characterized by a cold-water coral community dominated by the scleractinian coral Madrepora oculata, found in association with several invertebrate species including oysters, brachiopods and a variety of sponge species, as well as by a community dominated by cerianthids and sea urchins, mostly in sedimentary areas. The benthic communities identified in the area were then compared with habitats/biocenoses described in reference habitat classification systems that consider circalittoral and bathyal environments of the Mediterranean. The complex environmental setting characteristic of the marine area off Cap de Creus likely produces the optimal conditions for communities dominated by suspension- and filter-feeding species to develop. The uniqueness of this ecosystem and the anthropogenic pressures that it faces should prompt the development of effective management actions to ensure the long-term conservation of the benthic fauna representative of this marine area.